Exploring Multiculturalism and Intolerance: Understanding the Dynamics of Diversity - Sariyatun; Marpelina, Leni (Jurnal Pendidikan Multikultural Indonesia, 2023)
Amidst growing global challenges, multiculturalism and intolerance play a significant role in shaping a diverse society. Conflicts of interest and cultural differences often lead to intolerance, affecting social interactions and public policy. This research explores multiculturalism and intolerance to understand diversity dynamics in society. It utilizes a literature review, analyzing various journal articles and books relevant to the research topic. Additionally, this research reveals the complexity of the relationship between multiculturalism and intolerance. Factors such as cultural differences, identity politics, conflicts of interest, and social injustice are the main influences on the tolerance level in society. This research aims to analyze how these factors interact, evaluate their impact on multiculturalism and tolerance, and create strategies to enhance multicultural education and inclusive public policies. These findings emphasize the importance of multicultural education and inclusive public policy in promoting cross-cultural understanding and reducing prejudice. The implications of this research are the need for collaboration between the government, educational institutions, and civil society to strengthen multicultural education and implement inclusive policies that support tolerance and harmony between cultural groups. This research provides essential insights for strengthening multiculturalism and addressing societal intolerance through an approach focused on inclusivity and social justice.